Certain Relevant Issues of Interviewing Minors and Victims in the Practice of Law Enforcement Institutions During Criminal Proceedings - Pranka, Darius (Kriminologijos studijos, 2023)
Over a decade ago, an audit was conducted in Lithuania to assess the protection of children’s rights during criminal proceedings. The audit identified various shortcomings and issues related to child interviews. These problems were addressed in 2017 with the implementation of amendments to the Law on Criminal Procedure of the Republic of Lithuania, which have been in effect for over five years. This article aims to analyze the current practices, particularly in recent years, of law enforcement institutions when conducting interviews with minor witnesses and victims during criminal proceedings. Through analysis and empirical research, it was found that minors are frequently questioned outside of designated child interview rooms for unjustifiable reasons. Furthermore, their rights, particularly the right not to testify against their relatives or family members, are not always adequately explained to them. The legal significance of such procedural violations is discussed. Additionally, it is highlighted that employees of the Child Rights Protection and Adoption Service often lack proper preparation for conducting interviews with children. The article concludes by summarizing other findings from the empirical research.
Keywords: minor; survey; child’s interests; child’s rights